Letter - Sittingbourne Trades Council and Labour Party, 8 May 1926 (Sittingbourne)
1926-05-08 "Letter - Sittingbourne Trades Council and Labour Party, 8 May 1926" [g0308001.jpg], 8 May 1926 Local Organisation